Identifying an Optimal Cut-Off Point for Musculoskeletal Pain in the Upper Extremities to Prevent Lowered Work Performance. Issue 11 (November 2021) - Kwon, Suyoung; Lee, Soo-Jeong; de Castro, A.B.; Herting, Jerald R.; Bao, Stephen; Johnson, Kurt
Abstract : Objective: This study identified when musculoskeletal pain (MSP) in the upper extremities indicates lowered work performance to gauge when secondary prevention of musculoskeletal disorders is needed. Methods: Seven hundred thirty-three subjects from 12 manufacturing or healthcare facilities in Washington state participated. Work performance was measured by the Disabilities of the Arm, Shoulder and Hand work module (DASH-Work). Each DASH-Work score was compared to the mean among U.S. workers to determine if workers had lowered work performance. ROC curve analysis was conducted to find the cut-off in a composite MSP index (summing MSP intensities in shoulders, elbows/forearms, and hands/wrists; range 0 to 24) to detect lowered work performance. Results: The MSP index score of 2 achieved the best balance between sensitivity (0.79) and specificity (0.69) in detecting lowered work performance. Conclusions: To prevent reduced work performance, moderate or multisite pain may require proper management.